UPAYA MENINGKATKAN KEMAMPUAN MEMBACA HURUF HIJAIYAH MELALUI METODE PERMAINAN KARTU HURUF - Eka Dheasari, Agustiarini; Wulandari, Fitrianingsih; Ummah, Rofiatul; Trisnayanti Abdi, Fifit; Nisail Fitriah, Khoirotun (As-Sulthan Journal of Education, 2024)
This research aims to test the use of the letter card game method in an effort to improve the ability to read hijaiyah letters in group B children at RA Al-Husainiyah. The research method used is the PTK method carried out at RA Al-Husainiyah. This research design consists of 2 cycles with four stages, namely: planning, implementation, observation and reflection. Data collection techniques were carried out through observation and interviews. Meanwhile, data analysis was carried out using qualitative and quantitative descriptive methods. The results of this PTK research showed that there was an increase in the ability to read hijaiyah letters through the letter card game method that had been designed in group B, namely: in the pre-cycle the ability to read hijaiyah letters was stated to have not developed by 40%, was starting to develop by 50%, developed as expected by 10% , developing very well 0%, In cycle I it was stated that it had not developed at 20%, was starting to develop at 30%, developed according to expectations at 40%, developed very well at 10%. In cycle II, the initial increase in reading ability was stated as not yet developing at 0%, starting to develop at 10%, developing as expected at 60%, developing very well at 30%. From the results of this research, it can be concluded that there has been an increase in the ability to read hijaiyah letters through the letter card game method.